The interaction of clenbuterol hydrochloride with bovine hemoglobin using spectroscopic techniques and molecular modeling methods. Issue 5 (2009) - Wu Wu, Yun Yun; Mao Mao, Hui Hui; Zhao Zhao, Bo Bo; Shen Shen, Jian Jian
Abstract : The interaction of clenbuterol hydrochloride (CL) to bovine hemoglobin (BHb) under physiological conditions was investigated by using UV-vis absorption, fluorescence, circular dichroism (CD) and molecular modeling. The fluorescence intensity of BHb decreased regularly with the gradual increasing concentration of CL. It is observed that there was a prominent interaction between CL and BHb. The fluorescence data revealed that the fluorescence quenching is a static process, and the thermodynamic parameters were calculated according to the Van't Hoff equation. The alternations of protein secondary structure in the presence of CL were determined by the evidence of CD. Molecular modeling study that corroborate our experimental results revealed that the binding mode of CL–BHb complex could be attributed to the hydrophobic interaction and hydrogen bonding, but electronic interaction cannot be excluded.